Analisis Beban Kerja Terhadap Kualitas Layanan dan Kesejahteraan Tenaga Kesehatan Non ASN di Unit Rawat Inap Psikiatri Rsud Batara Guru Kabupaten Luwu - Aziz, Yuliana; Latu, Saparuddin; Jalal, Jalal; Yulis, Dian Meiliani; Rusli, Rusli (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
This study aims to analyze the relationship between work burden, service quality, and the well-being of non-ASN healthcare workers in the psychiatric inpatient unit of RSUD Batara Guru. The research used a quantitative correlational design (Kendall's Tau Test) with a cross-sectional approach. The data was collected from 30 non-ASN healthcare workers in the psychiatric inpatient unit using purposive sampling. The results showed that: (1) Work burden significantly affects service quality (ρ = 0.000 < 0.05), with a negative correlation indicating that higher work burden leads to lower service quality; (2) Work burden significantly affects the well-being of non-ASN healthcare workers (ρ = 0.010 < 0.05), with a negative correlation suggesting that higher work burden leads to lower well-being; (3) Service quality significantly affects the well-being of non-ASN healthcare workers (ρ = 0.001 < 0.05), with a positive correlation indicating that better service quality leads to better well-being. This research highlights the importance of managing work burden and improving service quality to enhance the well-being of healthcare workers.